Improving Students’ Scientific Literacy: Learning Studies Using Science Teaching Materials on Circulatory System Materials - Karimah, Karimah; Jufri, A. Wahab; Ramdani, Agus (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Scientific literacy is very important in determining the quality of education in a country. The importance of scientific literacy for students because it can invite students to understand the environment, health, economy and many other problems facing modern society. This study aim to develop an integrated science teaching material with guided inquiry model that appropriate to improve students’ scientific literacy. This research is a development research using the Dick & Carey model. In addition to developing science teaching materials, this research also develops syllabus, lesson plans, and scientific literacy instruments. This research was conducted in one of the NW MTs in West Lombok Regency. The validation of learning products was carried out by three validators, media experts and material experts. Expert validation data analysis was carried out using the Pearson validation formula. The results of the feasibility study of integrated science teaching materials using guided inquiry models obtained an average value of 94% with very valid criteria. The syllabus got an average score of 87%, lesson plans got an average score of 92%, and the scientific literacy instrument got an average score of 82%. In conclusion, the product of integrated science teaching materials with guided inquiry models is feasible to be implemented in learning process.